Two-way relaying protocol tailored for sensor network - Qing-feng ZHOU; Zhi-zhong DING; Cai-hong KAI (Tongxin xuebao)
A three-time-slot two-way relaying protocol,named as two-way selective decode-and-forward (TW-SDF) protocol,was proposed.This relaying protocol integrates network coding and the selective decode-and-forward method,and was tailored for wireless networks with simple devices,like sensor networks.Compared with the well-known physical-layer network coding protocol,the considered TW-SDF has the merits of full diversity order gain,low encoding and decoding complexity and easy-to-implement.Provided block codes,an upper bound on the block error rate of TW-SDF was derived and proved,which is valid for all hard decoders.Simulation results further verify that the upper bound is remarkably tight if BCH codes are utilized.